Meiotic behavior of small chromosomes in maize - Birchler, James A.; Han, Fangpu (Frontiers in Plant Science, 2013)
The typical behavior of chromosomes in meiosis is that homologous pairs synapse, recombine and then separate at anaphase I. At anaphase II, sister chromatids separate. However, studies of small chromosomes in maize derived from a variety of sources typically have failure of sister chromatid cohesion at anaphase I. This failure occurs whether there is pairing of two copies of a minichromosome or not. These characteristics have implications for managing the transmission of the first generation artificial chromosomes in plants. Procedures to address these issues of minichromosomes are discussed.